Perencanaan Strategis Sistem Informasi Koperasi Konsumen Warga Semen Gresik Dengan Pendekatan Enterprise Architecture Planning - Grandys Frieska Prassida; Mahara Rahma Maulida (Jurnal Teknologi Dan Sistem Informasi Bisnis, 2023)
The rapid development of the digital era has had a crucial impact on various industries, including business entities such as the Semen Gresik Citizens Consumer Cooperative, also known as KWSG. The implementation of Information Systems/Information Technology (IS/IT) in the digital transformation effort at KWSG is an important key, especially to realize the effectiveness and efficiency of business processes to lead to competitive advantage. However, in practice, IS/IT development still often encounters challenges in ensuring business and IS/IT strategies are aligned, or in other words IS/IT development initiatives must be able to meet current and future business needs. In addition, the increasingly complex development of IS/IT at KWSG can affect ongoing business processes if not planned properly. Therefore, this study aims to propose an IS/IT strategic plan that is useful for providing an overview of business models and current utilization of IS/IT in KWSG, as well as mapping future IS/IT development needs to produce relevant roadmap recommendations. . This study uses the Enterprise Architecture Planning (EAP) method approach which is supported by several analytical tools such as Value Chain diagram and McFarlan Strategic Grid to produce IS/IT strategic planning proposals at KWSG. The end result of IS/IT strategic planning in this study is to recommend 5 new application proposals and 1 application that needs to be developed which is mapped on the application development road map for the next 3 years.